10–14 Improving actor/patient recruitment for hils courses with support of the pioneer team academy. (17th November 2017) - Websdale, D; Edmond, S; Major, D; Backhouse, J; Peck, J; Howell, M; Wright, D; Purva, M
Abstract : Aim: Our aim was to increase our patient and actor database for the training courses we run at HILS and define a recruitment process. We planned to do this through the trust funded Pioneer Team Academy as they gave expert knowledgeable advice with each step of our project, as well as financial support. Method: We attempted to build interest in the following ways: Created posters, flyers and a pull-up, then distributed them throughout the hospital and local colleges. Visited medical outpatients and spoke with those visiting the clinics. Visited school careers fairs to discuss the project with prospective students. For those who signed up we created a basic induction which included a presentation, tour of the facility and an introduction to SimMan. Once completed, they were allowed to observe scenarios until they felt ready to act for HILS. Results: Working as the Pioneer Project team we have been very successful in achieving the majority of our objectives so far. Not only have we been able to recruit a sufficient number of actors and nurses to fill all the courses we are hosting this year, we are also oversubscribed with interest and continue to receive enquiries on a regular basis from prospective actors. This highlights the success of the promotional materials used for our campaign. We have attracted a higher calibre of actors through this programme as we recruited already professional actors, and have a much larger pool from which to select the most appropriate actor depending upon the course running. In order to continue to engage the actors we have implemented a policy of awarding certificates of recognition which we feel makes the programme mutually beneficial. Overall, not only has the project helped with actor and patient recruitment but it has also heightened the level of interest in what we offer as a department as a whole and the courses which we run. Conclusion: In order to develop and extend the project we have set objectives for the future. For the actor recruitment we aim to devise a full and comprehensive training programme which can be implemented. Within this programme we would like to design and develop the characters for each scenario so that the actors themselves are able to have input and are familiar with the roles they will undertake. For patient recruitment we wish to continue expanding the database so that we have sufficient numbers of patients available to allow us to take on extra courses and exams. To do this, we are working to establish a contact with a Consultant or Registrar within each of the main departments who will be able to help push recruitment in clinics and also triage the suitability of the patients being recruited.